Rhynchosia sousae (Leguminosae, Papilionoideae), a new species from eastern Mexico - Fortunato, Renee; Robbiati, Federico O. (Phytotaxa, 2014)
Rhynchosia sousae (Leguminosae, Papilionoideae) an endemic species from Veracruz State, in eastern Mexico, is described as new and illustrated. On account of its morphological features, it is assigned to sect. Rhynchosia. A table separating it from similar species: R. amabilis and R. precatoria, is presented, and its relationships and distinguishing characters are discussed.